Nausea and vomiting of pregnancy: Effects on quality of life and day‐to‐day function. (26th September 2017) - Tan, Amelia; Lowe, Sandra; Henry, Amanda
Abstract : Aims: To investigate the effect of nausea and vomiting of pregnancy (NVP) on quality of life (QoL) and activities of daily living/socioeconomic function in a contemporary Australian setting. Materials and Methods: Observational, single centre prospective cohort study using validated survey instruments in pregnant women at 9–16 weeks gestation at a tertiary metropolitan women's hospital in Sydney, Australia. QoL measured by the Short‐Form Health Survey (SF‐12) was compared between those with and without NVP. NVP severity scores were correlated with QoL scores, work patterns and medication use. Results: Of 116 participants, 72% had NVP, with no baseline (including mental health) differences between women with or without NVP. As classified by modified Pregnancy‐Unique‐Quantified‐Emesis (PUQE) survey, 42% had mild symptoms, 55% moderate and 1% severe. SF‐12 Physical Component Summary (PCS) scores were significantly lower for those with NVP ( P  <   0.001), but not Mental Component Summary (MCS) scores ( P  =   0.11). Decreasing QoL was associated with increasing NVP severity ( P  <   0.001), most markedly in the physical domain ( P  <   0.001). Only 39% of women used any NVP treatment and 15% pharmacotherapy. Most used treatments were vitamin B6, ginger, metoclopramide and natural remedies. Significantly more women with NVP required time off work (45% vs 16%, P  =   0.003). Conclusions: NVP is a physically morbid disease, affecting most pregnancies. NVP has a significant detrimental impact on QoL, especially physical QoL and work function. Despite this, we found low treatment utilisation, even in those with moderate/severe symptoms. Women should be encouraged to seek assistance for NVP and further education is required to improve practitioner awareness and management.